Studi Literature: Pengaruh Teknik Audit Investigatif, Pengalaman Dan Profesionalisme Auditor Investigatif Dalam Pengungkapan Fraud - Moch Deny Setiawan; Tri Ratnawati (Jurnal Riset Akuntansi, 2024)
This research aims to determine the influence of investigative audit techniques, experience and professionalism of investigative auditors on fraud disclosure. The research method used in this research is literature study. The results of this research are that investigative audit techniques have no effect on disclosure of fraud, experience has an effect on disclosure of fraud, professionalism of investigative auditors has a positive effect on disclosure of fraud. Further research is still needed to add variables such as forensic accounting, investigative auditing, professional skepticism, independence and code of ethics.